UV RESISTANCE LOCUS 8 From Chrysanthemum morifolium Ramat (CmUVR8) Plays Important Roles in UV-B Signal Transduction and UV-B-Induced Accumulation of Flavonoids - Yang, Yanjun; Yang, Xiuli; Jang, Zhifang; Chen, Zhehao; Ruo, Xiujun; Jin, Weiyang; Wu, Ying; Shi, Xiaojing; Xu, Maojun (Frontiers in Plant Science, 2018)
UV Resistance Locus 8 (UVR8), an ultraviolet-B (UV-B; 280-315 nm) photoreceptor, participates in the regulation of various plant growth and developmental processes. UV-B radiation is an important factor enhancing the production of active components in medicinal plants. To-date, however, studies on UV-B photoreceptors have largely focused on Arabidopsis, and the functions of UVR8 in medicinal plants are still largely unknown. In the present study, a homologue of Arabidopsis UVR8, CmUVR8, was isolated from Chrysanthemum morifolium Ramat, and its structure and function were analyzed in detail. Protein sequence analysis showed that CmUVR8 contained nine conserved regulators of chromosome condensation 1 repeats, seven conserved bladed propellers, one C27 region, three “GWRHT” motifs and several crucial amino acid residues (such as 14 Trps and 2 Args), similar to AtUVR8. 3-D structural analysis of CmUVR8 indicated that its structure was similar to AtUVR8. Heterologous expression of CmUVR8 could rescued the deficient phenotype of uvr8-6, a mutant of UVR8 in Arabidopsis, indicating the role of CmUVR8 in the regulation of hypocotyl elongation and HY5 gene expression under UV-B irradiation. Moreover, CmUVR8 regulates UV-B-induced expression of four flavonoids biosynthesis-related genes and the UV-B-induced accumulation of flavonoids. Furthermore, the interaction between CmUVR8 and CmCOP1 were confirmed using a yeast two-hybrid assay. These results indicated that CmUVR8 plays important roles in UV-B signal transduction and the UV-B-induced accumulation of flavonoids, as a counterpart of AtUVR8.